Roman Catholicism in the United States : A Thematic History - Fisher, James Terence; McGuinness, Margaret M. (Book collections on Project MUSE., 2019)
A collection of essays examining Catholicism in the United States from a variety of perspectives. The volume is divided into three sections: ""'Beyond the Parish, ' 'Presence in the World, ' and 'Prophetic Catholicism'."" Essay topics include: anti-Catholicism, women religious, Latino/a Catholicism, Catholicism and Popular Culture, and Rural Catholcism